Muscle cells of sporadic amyotrophic lateral sclerosis patients secrete neurotoxic vesicles. Issue 2 (22nd February 2022) - Le Gall, Laura; Duddy, William J.; Martinat, Cecile; Mariot, Virginie; Connolly, Owen; Milla, Vanessa; Anakor, Ekene; Ouandaogo, Zamalou G.; Millecamps, Stephanie; Lainé, Jeanne; Vijayakumar, Udaya Geetha; Knoblach, Susan; et al.
Abstract: Background: The cause of the motor neuron (MN) death that drives terminal pathology in amyotrophic lateral sclerosis (ALS) remains unknown, and it is thought that the cellular environment of the MN may play a key role in MN survival. Several lines of evidence implicate vesicles in ALS, including that extracellular vesicles may carry toxic elements from astrocytes towards MNs, and that pathological proteins have been identified in circulating extracellular vesicles of sporadic ALS patients. Because MN degeneration at the neuromuscular junction is a feature of ALS, and muscle is a vesicle‐secretory tissue, we hypothesized that muscle vesicles may be involved in ALS pathology. Methods: Sporadic ALS patients were confirmed to be ALS according to El Escorial criteria and were genotyped to test for classic gene mutations associated with ALS, and physical function was assessed using the ALSFRS‐R score. Muscle biopsies of either mildly affected deltoids of ALS patients ( n = 27) or deltoids of aged‐matched healthy subjects ( n = 30) were used for extraction of muscle stem cells, to perform immunohistology, or for electron microscopy. Muscle stem cells were characterized by immunostaining, RT‐qPCR, and transcriptomic analysis. Secreted muscle vesicles were characterized by proteomic analysis, Western blot, NanoSight, and electron microscopy. The effects of muscle vesicles isolated from the culture medium of ALS and healthy myotubes were tested on healthy human‐derived iPSC MNs and on healthy human myotubes, with untreated cells used as controls. Results: An accumulation of multivesicular bodies was observed in muscle biopsies of sporadic ALS patients by immunostaining and electron microscopy. Study of muscle biopsies and biopsy‐derived denervation‐naïve differentiated muscle stem cells (myotubes) revealed a consistent disease signature in ALS myotubes, including intracellular accumulation of exosome‐like vesicles and disruption of RNA‐processing. Compared with vesicles from healthy control myotubes, when administered to healthy MNs the vesicles of ALS myotubes induced shortened, less branched neurites, cell death, and disrupted localization of RNA and RNA‐processing proteins. The RNA‐processing protein FUS and a majority of its binding partners were present in ALS muscle vesicles, and toxicity was dependent on the expression level of FUS in recipient cells. Toxicity to recipient MNs was abolished by anti‐CD63 immuno‐blocking of vesicle uptake. Conclusions: ALS muscle vesicles are shown to be toxic to MNs, which establishes the skeletal muscle as a potential source of vesicle‐mediated toxicity in ALS.